Membrane Interlayer with Pt Recombination Particles for Reduction of the Anodic Hydrogen Content in PEM Water Electrolysis. Issue 16 (1st January 2018) - Klose, C.; Trinke, P.; Böhm, T.; Bensmann, B.; Vierrath, S.; Hanke-Rauschenbach, R.; Thiele, S.
Abstract : Polymer electrolyte membrane (PEM) water electrolysis is a key technology for sustainable hydrogen based energy supply. Gas permeation through the PEM leads to hydrogen in oxygen at the anode side posing a safety hazard and therefore restricting the operation window of PEM water electrolysis, especially when operating under pressure. In this work the hydrogen in oxygen content at the anode is significantly reduced when a recombination interlayer is integrated into the membrane electrode assemblies (MEAs) compared to reference MEAs without interlayer. The recombination interlayer with a platinum loading of 0.02 mg cm − 2 is sprayed between two membranes that are coated with anode and cathode catalysts on the outside. The permeating H2 and O2 forms water at the recombination interlayer, leading to higher gas purity and resolving safety issues. In case of the MEAs with interlayer also a constant current hold at 1 A cm − 2 for 245 h revealed only a slight increase of the hydrogen in oxygen content (below 140 · 10 − 6 vol.% h − 1 ) whereas for the reference MEAs without interlayer a stronger increase was observed (above 1250 · 10 − 6 vol.% h − 1 ). Furthermore, the long-term experiments showed no increased degradation rates compared to the reference MEAs.